Effet de l’épandage des biomasses fraiches de Tithonia diversifolia et de Tephrosia vogelii sur la croissance et le rendement de quatre variétés locales de Haricot commun (Phaseolus vulgaris L.) à Lubumbashi, R.D.Congo. - Ilunga, Masengo; Mbgam M.S. (Centre de documentation de l'enseignement superieur et universitaire et de la recherche de Kinshasa, 2016)
A study was conducted on a ferralsol in southern DR Congo to assess the effects of spreading Tithonia diversifolia (Td) and Tephrosia vogelii (Tv) leaves on yields of four local varieties of common bean (Kasungeji, D6 Kenya, local white bean and Kigoma). The experimental design was a randomized complete block design with three replications and twelve treatments:T1(V1 and 5tTd); T2(V2 and 5t Td); T3(V3 and 5tTd); T4(V4 and 5tTd); T5(V1 and 5tTv); T6(V2 and 5tTv); T7(V3 and 5tTv); T8(V4 and 5tTv); T9(V1,0tTd and 0tTv); T10(V2,0tTd and 0tTv); T11(V3,0tTd and 0tTv); T12(V4, 0tTd and 0tTv). Observations were made on growth parameters and yield. Significant differences were found between the treatments on plant height (P≤0, 05) which varies between 25 and 38 cm and yields (P≤0,000) ranging from 186, 7 and 986, 7 Kg/Ha; treatments T1 that gave the highest yields whereas T12 gave the lowest. The general trend in the productivity of plots was in the following order T1>T2>T4>T3>T6>T7>T10>T5>T11>T9>T8>T12. Under the conditions of this trial, the use of biomass of Tithonia and Tephrosia, mulchis is better suited for small income rural farmers because it can enrich soil with organic matter and nutrients through degradation of mulching material and repel insects.